2004
DOI: 10.1063/1.1771808
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric and electrical behavior of (Na0.5Bi0.5)TiO3 thin films

Abstract: Sodium bismuth titanate (Na0.5Bi0.5)TiO3 (NBT) of perovskite structure is among the best known lead-free piezoelectric∕ferroelectric that promises a number of applications in sensors and actuators. However, NBT in thin film form has not been properly investigated, although NBT in bulk ceramic form has been widely studied. In this letter, we report the growth of polycrystalline NBT thin films by radio-frequency magnetron sputtering and their ferroelectric behavior. The NBT thin films exhibit a well-defined hyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
56
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(61 citation statements)
references
References 20 publications
5
56
0
Order By: Relevance
“…It can be seen that 0.82NBT-0.18ST thin films' crystallization has been well finished at 650 • C, whereas when annealed at 700 • C, its crystallization is reduced due to excess loss of bismuth. The similar change in crystallization with temperatures has also been observed in NBT film of which the annealing temperatures were 50 • C higher on average [17]. A secondary phase is clearly observed in the XRD pattern.…”
Section: Methodssupporting
confidence: 75%
See 1 more Smart Citation
“…It can be seen that 0.82NBT-0.18ST thin films' crystallization has been well finished at 650 • C, whereas when annealed at 700 • C, its crystallization is reduced due to excess loss of bismuth. The similar change in crystallization with temperatures has also been observed in NBT film of which the annealing temperatures were 50 • C higher on average [17]. A secondary phase is clearly observed in the XRD pattern.…”
Section: Methodssupporting
confidence: 75%
“…A secondary phase is clearly observed in the XRD pattern. The same phase exists in NBT thin films obtained by sol-gel + spin coating [16][17][18] and radio-frequency magnetron sputtering [17], which is considered respectively as an amorphous phase that depended significantly on thermal annealing condi- tions and Bi 2 Ti 2 O 7 phase that could be reduced at an annealing temperature higher than 600 • C in oxygen atmosphere. From Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The scientific community has intensively searched for and studied Pb-free piezoelectric materials. Among the few Pb-free materials available, solid solutions based on (Bi 0.5 Na 0.5 )TiO 3 (BNT) (Isupov, 2005;Zhou et al, 2004;Park et al, 1996;Tu et al, 1994;Zvirgzds et al, 1982;Pronin et al, 1980;Jaffe et al, 1971) and (Na 0.5 K 0.5 )NbO 3 (NKN) (Dai et al, 2009;Wang et al, 2007;Saito et al, 2004;Tennery & Hang, 1968;Haertling, 1967;Jaeger & Egerton, 1962;Egerton & Dillon, 1959) with a morphotropic phase boundary (MPB) have been considered as potential candidates for replacing PZT. Each material has its merits and demerits.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the grain boundary can change the control mechanism of electrical behavior with increasing temperature. 24 Compared to the polycrystalline films, the epitaxial film, as an alternative for single crystal, can reduce the influence of defects and hence improve the thermostability of energy storage properties. It has been reported that the density of defects is reduced, and the mobility of the domain wall is improved in epitaxial PLZT thin films.…”
mentioning
confidence: 99%